1998
DOI: 10.1182/blood.v91.10.3601
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Cost Effectiveness of a 10 × 109/L Trigger for Prophylactic Platelet Transfusions Compared With the Traditional 20 × 109/L Trigger: A Prospective Comparative Trial in 105 Patients With Acute Myeloid Leukemia

Abstract: In 105 consecutive patients with de novo acute myeloid leukemia (French-American-British M3 excluded), we compared prospectively the risk of bleeding complications, the number of platelet and red blood cell transfusions administered, and the costs of transfusions using two different prophylactic platelet transfusion protocols. Two hundred sixteen cycles of induction or consolidation chemotherapy and 3,843 days of thrombocytopenia less than 25 × 109/L were evaluated. At the start of the study, each of the 17 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
101
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(105 citation statements)
references
References 18 publications
1
101
0
3
Order By: Relevance
“…There is a view that most prophylactic transfusions are clinically unnecessary even at a threshold of 10 × 9 L −1 (Gaydos et al ., 1962; Roy et al ., 1973), and some groups are suggesting avoiding the use of prophylactic platelets completely and the decision to administer platelets should incorporate individual clinical characteristics of the patient and not be a reflexive reaction to the platelet count (Wandt et al ., 1998; Wandt et al ., 2001). For example, in autograft patients, we can predict platelet regeneration 24–48 h after a rise in the IPF percentage.…”
Section: Discussionmentioning
confidence: 99%
“…There is a view that most prophylactic transfusions are clinically unnecessary even at a threshold of 10 × 9 L −1 (Gaydos et al ., 1962; Roy et al ., 1973), and some groups are suggesting avoiding the use of prophylactic platelets completely and the decision to administer platelets should incorporate individual clinical characteristics of the patient and not be a reflexive reaction to the platelet count (Wandt et al ., 1998; Wandt et al ., 2001). For example, in autograft patients, we can predict platelet regeneration 24–48 h after a rise in the IPF percentage.…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between thrombocytopenia and an increased risk of bleeding has clearly been established and platelet (PLT) transfusions are effective in decreasing the bleeding risk and therapy‐related mortality in thrombocytopenic patients 1,2 . Recommendations for PLT transfusions are based on a variety of retrospective and prospective studies supporting a transfusion threshold of 5 × 10 9 to 10 × 10 9 /L in the absence of plasmatic coagulation abnormalities 3‐10 . Prophylactic transfusion of PLTs above this threshold is generally not recommended and the benefits of PLT transfusions must be balanced carefully against the potential risks of any transfusion.…”
mentioning
confidence: 99%
“…Traditionally, the transfusion trigger has been set at 20 × 10 9 PLTs per L on the basis of a study performed in the early 1960s, which showed that severe hemorrhages rarely occurred in patients above this limit, in spite of widespread aspirin use 13 . In recent years, a lower “safe” threshold has been used in patients with various conditions 14‐22 . Several of those authors also reported a significant reduction in the use of PLT transfusions with a lower threshold 15,16,18,19,21 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a lower “safe” threshold has been used in patients with various conditions 14‐22 . Several of those authors also reported a significant reduction in the use of PLT transfusions with a lower threshold 15,16,18,19,21 . Previously, only one randomized prospective study in HPCT recipients had been published.…”
Section: Discussionmentioning
confidence: 99%